Language, Deals, and Standards: The Future of XML Contracts - Lawrence A. Cunningham (Washington University Law Review, 2006)
eXtensible Markup Language (XML) structures information in documentary systems ranging from financial reports to medical records and business contracts. XML standards for specific applications are developed spontaneously by self-appointed technologists or entrepreneurs. XML's social and economic stakes are considerable, especially when developed for the private law of contracts. XML can not only can reduce transaction costs but also limit the range of contractual expression and redefine the nature of law practice. Thus reliance on spontaneous development may be sub-optimal and identification of a more formal public standard-setting model necessary. To exploit XML's advantages while minimizing risks, this Article envisions creating a publicly oriented foundation to set XML-based standards for the private law of corporate contracts. The Article's specific inquiry concerning corporate contracts illuminates XML's broader implications, making the standard-setting model it contributes adaptable to other contexts.
Keywords: XML (Document markup language); Contracts – Legal composition; Corporate lawyers